Pengaruh Kesadaran Merek, Asosiasi Merek, dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Minute Maid Pulpy (Studi pada Konsumen Minute Maid Pulpy di Kecamatan Banyumanik) - Inggarrestu Pradiptaningtyas; Agus Hermani (Universitas Diponegoro, 2017)
Hight of consumer puschashing desicion is a hope that is always wanted by every industry so the product which is marketed can be sold out that operasional activity from the industry keep on state smoothly. The brand awareness, brand asosiation, and product quality is one of factors that can affect the high-low level of purchasing desicion at the purchasing of Minute Maid Pulpy. As the hight of brand awareness at Minute Maid Pulpy from consumer, the strength of brand asosiation from consumer towards Minute Maid Pulpy, and the hight of product quality awarding from Minute Maid Pulpy for consumer, so it will rise the purchasing decision level of Minute Maid Pulpy’s consumer.The research type used explanatory, amount of sample is 100 respondents who is taken on 3 urban villages at Banyumanik. Data collection used questionnaire with likert measurement scale. Data analysis method used validity and reability test, correlation coefficient (R), simple linear regression, multiple linear regression, coefficicient of determination (R2), F test, and t test. The result of this research concluded that brand awareness, brand asosiation, and brand quality have a strong effect that positive and significant to purchasing decision, whether partially nor simultaneosly. Brand awareness, brand association and product quality bring a strong effect to purchasing decision that is proved with the amount of its correlation coefficient (R) is 0.784.